The role of social movements in transformative tourism development: Lessons learnt from a case study in Lithuania - Vidickiene, Dalia; Gedminaite-Raudone, Zivile; Simonaityte, Vitalija; Lankauskiene, Rita (European Spatial Research and Policy, 2023)
This study responds to the need for theoretical and empirical research on value co-creation in tourism. Previous research has mainly adopted a perspective centred on the collaborative relationships between tourists and service providers, i.e., has been focused on a relationship called ‘one-to-one’. According to the emerging trends in value co-creation theory, value co-creation activities, however, are more complex. The research provides empirical support to previous general conceptualisations of value-creation and brings some new insights to value co-creation involving multiple actors from a perspective called ‘many-to-one’. The research is focused on the role of the most active stakeholder in transformative tourism that represents ‘many’ actors as a whole – the social movement. The paper describes a case on a transformative tourism initiative that is a particularly rich setting for expanding value-cocreation in a network of activities’ research for a more complex understanding of value networks in the tourism sector. The case study examines extensively the role of social movements in transformative tourism development through value co-creation. The findings develop a more complex value co-creation mechanism and enable the conceptualisation of the value co-creation process by identifying drivers of collaboration, value co-creation activities, and outcomes. The research demonstrates the potential of social movements for the development of transformative tourism in value co-creation and has implications for both entrepreneurs and policymakers seeking to develop transformative tourism and leaders of a new generation of social movements aiming to transform society.